Efficient sensor position selection using graph connectivity / Firdawati Mohamed ...[et al.] - Mohamed, Firdawati; Abd Ghani, Nurul Nadiah; Ismail, Mardhiyah; Salleh Huddin, Nur Shamimi; Wan Hassan, Wan Nur Hafawati (Unit Penerbitan UiTM Kelantan, 2018)
The traffic control has to be managed systematically to avoid the traffic congestion especially in the busy city. The efficient and systematic traffic control is studied in this research using the connectivity and compatibility graphs of traffic intersections. From the graphs drawn, the most efficient route can be determined and the capacity of traffic flow can be maximized by finding the minimum number of edges or the minimum number of vertices. In this paper, the 4-ways intersection stream at Jalan Membunga Machang is chosen to find suitable locations to place sensors that are used to collect traffic data. From the graphs obtained, there are 12 vertices identified where 36 edges were connected to it. By using the algorithm of graph theory, four sets of minimal edge control were determined and these edges were validated using the MAPLE software